Educational Quiz Game Media Nazo nazo for Basic Level Choukai Learning - Ikhsan, Juniardi; Herniwati, Herniwati; Rasiban, Lina Meilia (Universitas Muhammadiyah Yogyakarta, 2025)
Nazo-nazo is a type of riddle game that is quite popular in Japan. This game is usually designed for children, where they guess an object through images or riddles narrated by others. However, in this study, nazo-nazo is used as an educational quiz game media for basic Japanese listening learning, as games specifically designed to improve Japanese listening skills are still relatively rare. This study aims to determine the listening skills of basic Japanese learners before and after the implementation of the nazo-nazo game media and to identify which listening skill instruction is more effective between the experimental and control classes through a comparative statistical test. Additionally, it evaluates students' responses to this game. The research method used is quantitative. The total sample consists of 42 participants, divided into two groups: 22 students in the experimental group and 20 students in the control group. The results show that the post-test scores were higher than the pre-test scores in the experimental class, with an average post-test score of 82.95, compared to an average pre-test score of 64.56. The t-test calculation resulted in a value of 4.945, which is greater than the t-table value of 2.02 (at a 5% significance level). This indicates that using the nazo-nazo quiz game as a media for teaching listening skills is more effective than teaching without it. Additionally, the questionnaire results show that respondents gave positive perceptions of the nazo-nazo quiz game media, as it creates a new learning atmosphere and increases learning motivation. Therefore, this game can be applied as an alternative method for teaching basic Japanese listening skills.